MXene / rGO aerogel composite material as well as preparation method and application thereof
By adjusting the pH value and infrared light irradiation treatment in the aqueous solution, the high energy consumption and structural damage problems in the improvement of GO conductivity are solved, the effective coupling between MXene and rGO is achieved, and the electromagnetic wave absorption performance is improved.
Patent Information
- Application Number
- CN202411461589.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has problems such as high energy consumption, structural damage, use of toxic reducing agents and reduced interface polarization effects when improving the conductivity of graphene oxide (GO), resulting in limited application in the field of electromagnetic wave absorption.
By adjusting the pH value of MXene and GO in an aqueous solution, promoting its coupling, and using infrared light irradiation to induce temperature, dissociating and removing oxygen-containing functional groups from GO at low energy consumption, forming a three-dimensional MXene/rGO aerogel, realizing Improved conductivity.
It realizes good compatibility and interface connection between MXene and rGO, improves the conductive performance and electromagnetic wave attenuation performance of the material, avoids structural damage and high energy consumption, and obtains excellent wave absorption performance.
Smart Images

Figure HDA0005092016300000011 
Figure HDA0005092016300000012 
Figure HDA0005092016300000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of electromagnetic wave absorbing (wave absorbing) materials, and specifically relates to a MXene / rGO aerogel composite material and a preparation method and application thereof. Background Art
[0002] The widespread application of electromagnetic wave technology has exacerbated the negative impact of electromagnetic radiation on human health, the stable operation of electronic devices and the natural environment. Therefore, the development of high-performance electromagnetic wave absorbing (absorbent) materials has important practical significance. Graphene oxide (GO) has great application potential in the field of wave absorption due to its light weight, large specific surface area, strong polarization loss and adjustable chemical properties. However, the presence of a large number of oxygen-containing functional groups on the surface of GO significantly reduces its conductivity, which in turn limits its practical application in the field of electromagnetic wave absorption.
[0003] Currently, improving the conductivity of GO is mainly achieved through two methods.
[0004] The first method is to perform a reduction treatment on it to generate reduced graphene oxide (rGO). Common reduction techniques include chemical reduction, thermal reduction, electrochemical reduction, microwave reduction, and ultraviolet / laser reduction. Among these methods, the chemical reduction method effectively removes oxygen-containing functional groups by using reducing agents (such as hydrazine, hydrazine hydrate, ascorbic acid, etc.), but some reducing agents (such as hydrazine) are highly toxic and pose a potential threat to the environment and human health. In addition, the chemical reduction process can easily cause damage to the graphene structure or introduce additional defects, thereby affecting its physical properties. The thermal reduction method removes oxygen-containing functional groups at high temperatures and restores the sp 2 Although this method has a certain effect in improving the conductivity of graphene, it has high energy consumption and usually requires a high temperature of more than 200°C. In addition, the reaction process has high requirements for the control of the reducing atmosphere, which to a certain extent limits its further promotion and application. Although the electrochemical reduction method can accurately control the degree of reduction and avoid over-reduction or structural damage, its efficiency is low and the cost of electrochemical equipment is high. The microwave reduction method has low energy consumption, but it is difficult to accurately control the degree of reduction during the reduction process. UV / laser reduction does not require the use of chemical reagents and can locally reduce GO, but it requires special laser or light source equipment, which has significant limitations in actual operation.
[0005] The second method to improve the conductivity of GO is to combine it with highly conductive materials. Common conductive materials include metal nanoparticles (such as gold, silver, copper), conductive polymers (such as polyaniline, polypyrrole), carbon nanomaterials (such as carbon nanotubes, carbon black) and two-dimensional materials (such as MXene).
[0006] As an emerging two-dimensional nanomaterial, MXene has shown broad application potential in the field of wave absorption due to its efficient photothermal conversion ability, excellent electrical conductivity and significant dielectric loss characteristics. Chinese patent CN116351403B discloses a MXene / rGO aerogel, the preparation method of which is as follows: a MXene dispersion and a GO dispersion are mixed in an ice-water bath to obtain a MXene / GO mixed dispersion, and a MXene / rGO hydrogel is prepared by an ice template-assisted stepwise chemical reduction-induced self-assembly strategy, followed by freeze drying to obtain a MXene / rGO aerogel. Chinese patent CN108489644B discloses a MXene / rGO composite three-dimensional structure, the preparation method of which is as follows: a MXene solution is added to a GO nanosheet colloidal solution, mixed evenly, and then the mixed solution is subjected to vacuum freeze-drying and annealing to obtain a corresponding three-dimensional composite material. Although the above methods improve the conductivity of GO to a certain extent by forming a composite material with MXene, the composite materials prepared by these methods, in which MXene is easily unevenly distributed or agglomerated in the GO sheets, limit the electron transmission efficiency, and thus it is difficult to effectively improve the conductivity loss of the material. In addition, the above problems will also lead to a weakening of the interface polarization effect, further resulting in a reduction in polarization loss, which is not conducive to its application in the field of wave absorption. In addition, the chemical reduction method used in the above method may also cause graphene structural damage or defects, and the thermal reduction method faces a high energy consumption problem, which in turn affects the effectiveness and practicality of the above method. Summary of the invention
[0007] In order to solve the above-mentioned problems of the prior art, the present invention provides a MXene / rGO aerogel composite material and a preparation method and application thereof. The preparation method can achieve good compatibility and interface connection between MXene and rGO in the composite material, and can reduce GO efficiently, simply and with low energy consumption.
[0008] The present invention is achieved through the following technical solutions:
[0009] The present invention provides a method for preparing a MXene / rGO aerogel composite material, comprising the following steps:
[0010] S1, adding MXene and GO into water and dispersing them by ultrasonic to obtain a mixed dispersion;
[0011] S2, adding an acidic reagent dropwise to the mixed dispersion, adjusting the pH to 4-6, and dispersing by ultrasonication to obtain an acidic mixed solution;
[0012] S3, freeze-drying the acidic mixed solution to obtain a three-dimensional MXene / GO aerogel composite material;
[0013] S4, subjecting the three-dimensional MXene / GO aerogel composite material to infrared light irradiation treatment to obtain a three-dimensional MXene / rGO aerogel composite material.
[0014] Preferably, in S1, the mass ratio of MXene to GO is (10-50):(90-50).
[0015] Preferably, the MXene is Ti3C2T x .
[0016] Preferably, in S1, the ultrasonic dispersion time is 10 to 30 minutes.
[0017] Preferably, in S2, the acidic reagent is a hydrochloric acid solution.
[0018] Preferably, in S2, the ultrasonic dispersion time is 10 to 30 minutes.
[0019] Preferably, in S3, the freeze-drying conditions are: vacuum degree of 3 to 10 Pa, temperature of -30 to -40°C, and freeze-drying time of 40 to 60 h.
[0020] Preferably, in S4, the infrared light irradiation treatment time is 10 to 30 seconds.
[0021] The present invention also provides a MXene / rGO aerogel composite material obtained by the preparation method as described above.
[0022] The present invention also provides the use of the MXene / rGO aerogel composite material as an absorbing material in electromagnetic wave absorption.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] Since the acidic oxygen-containing functional groups of GO and MXene in the aqueous solution will be ionized and dissociated into hydrogen protons, the two will be negatively charged, which will increase the electrostatic repulsion between the two, so that the two cannot be effectively coupled. To this end, the present invention adjusts the pH value of the mixed dispersion of MXene and GO by an acidic reagent, changes the acidity and alkalinity of the system, and promotes the dissociation equilibrium to move to the left by lowering the pH value, thereby reducing the electrostatic repulsion between GO and MXene nanosheets. Through the above adjustment, the distance between MXene and GO sheets is reduced, and effective coupling between GO and MXene is achieved by dimensional matching. Subsequently, a three-dimensional MXene / GO aerogel structure is obtained by freeze-drying technology. Finally, low-energy infrared light irradiation is adopted, and the excellent photothermal effect of MXene is utilized to absorb the energy of infrared light, induce an instantaneous increase in temperature, and is conducive to promoting the dissociation and removal of oxygen-containing functional groups (such as carboxyl, hydroxyl and epoxy groups) in the three-dimensional MXene / GO aerogel structure. At the same time, during this deoxygenation process, the excellent conductivity of MXene is conducive to stimulating electron migration, thereby initiating further chemical reactions, decomposing the oxygen-containing functional groups of GO, and forming a three-dimensional MXene / rGO aerogel. The present invention achieves good compatibility and interface connection in the composite material by rationally designing the dimensional matching of MXene and GO; with the help of the excellent conductivity and photothermal response characteristics of MXene, GO can be efficiently, simply and energy-efficiently reduced by infrared light irradiation, further ensuring that its conductive properties are effectively improved. The preparation method of the present invention has the advantages of simple operation, will not cause damage or defects in the graphene structure, and has low energy consumption. The obtained three-dimensional MXene / rGO aerogel has excellent wave absorption performance.
[0025] The MXene / rGO aerogel composite material prepared by the present invention has good electrical conductivity and excellent electromagnetic wave attenuation performance, and can be used as an absorbing material in the field of electromagnetic wave absorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The SEM image, XRD image and three-dimensional reflection loss image of the material prepared in Example 1 of the present invention.
[0028] Figure 2 This is a three-dimensional reflection loss diagram of the material prepared in Example 2 of the present invention.
[0029] Figure 3This is a three-dimensional reflection loss diagram of the material prepared in Example 3 of the present invention.
[0030] Figure 4 This is a three-dimensional reflection loss diagram of the material prepared in Example 4 of the present invention.
[0031] Figure 5 This is a three-dimensional reflection loss diagram of the material prepared in Example 5 of the present invention.
[0032] Figure 6 This is a three-dimensional reflection loss diagram of the material prepared in Example 6 of the present invention.
[0033] Figure 7 This is a three-dimensional reflection loss diagram of the material prepared in Example 7 of the present invention.
[0034] Figure 8 The XRD diagram and three-dimensional reflection loss diagram of the material prepared in Comparative Example 1.
[0035] Fig. 9 This is the three-dimensional reflection loss diagram of comparative example 2.
[0036] Fig.10 The XRD diagram and three-dimensional reflection loss diagram of the material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0037] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0038] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art.
[0039] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.
[0040] The method for preparing the MXene / rGO aerogel composite material of the present invention comprises the following steps:
[0041] S1, adding MXene and GO into water and dispersing them by ultrasonic to obtain a mixed dispersion;
[0042] S2, adding an acidic reagent dropwise to the mixed dispersion, adjusting the pH to 4-6, and dispersing by ultrasonication to obtain an acidic mixed solution;
[0043] S3, freeze-drying the acidic mixed solution to obtain a three-dimensional MXene / GO aerogel composite material;
[0044] S4, subjecting the three-dimensional MXene / GO aerogel composite material to infrared light irradiation treatment to obtain a three-dimensional MXene / rGO aerogel composite material.
[0045] The present invention adjusts the pH value of the mixed dispersion of MXene and GO to acidic by an acidic reagent, so that the ionization equilibrium of the acidic groups on the surface of MXene and GO moves to the left, reduces the electrostatic repulsion between GO and MXene nanosheets, reduces the distance between the sheets, and realizes the coupling of the two by dimensional matching. Subsequently, a three-dimensional MXene / GO aerogel composite structure is obtained by freeze-drying technology. Finally, by low-energy infrared light irradiation, the excellent photothermal effect and conductivity of MXene are utilized to promote the dissociation and removal of oxygen-containing functional groups (such as carboxyl, hydroxyl and epoxy groups) in GO. During the reduction process of GO, the excellent conductivity of MXene is conducive to exciting electron migration and decomposing oxygen-containing functional groups, thereby obtaining a three-dimensional MXene / rGO aerogel composite material with excellent wave absorption performance.
[0046] The above-mentioned preparation method of the present invention realizes the compatibility and matching of rGO and MXene systems, solves the problems of high energy consumption and easy generation of harmful substances in the GO reduction process, and thus produces a MXene / rGO aerogel composite material with excellent electromagnetic wave absorption performance, which has significant advantages in the fields of stealth, biomedicine, etc.
[0047] The GO used in the present invention can be prepared by a modified Hummers method, and the MXene used can be prepared by a wet chemical etching method. x .
[0048] As a preferred embodiment, in the above method, the mass ratio of MXene to GO is (10-50):(90-50). The mass ratio of MXene to GO has a certain influence on the wave absorbing properties of the final composite material. By controlling the appropriate mass ratio, a MXene / rGO aerogel composite material with excellent wave absorbing properties can be obtained.
[0049] As a preferred solution, in the above methods S1 and S2, the ultrasonic dispersion time is 10 to 30 minutes, which can achieve sufficient dispersion of MXene and GO.
[0050] In the method of the present invention, S3 specifically comprises: using liquid nitrogen to quickly freeze the acidic mixed solution for 20-30 minutes, and then transferring the frozen solid to a freeze dryer for freeze drying.
[0051] As a preferred embodiment, the freeze-drying conditions adopted in the present invention are: vacuum degree of 3 to 10 Pa, temperature of -30 to -40°C, and freeze-drying time of 40 to 60 hours.
[0052] In S4 of the present invention, an infrared lamp is used to irradiate the MXene / GO aerogel composite material for 10 to 30 seconds to obtain a MXene / rGO aerogel composite material.
[0053] Since the MXene combined with infrared light irradiation reduction treatment in the present invention improves the poor conductivity of GO, it promotes the transmission of electrons and increases the conductivity loss. In addition, the dimensional matching of the designed two-dimensional MXene and two-dimensional rGO promotes the interface polarization effect, synergistically optimizes the impedance matching, and solves the problem of poor conductivity of GO. Therefore, the present invention produces a MXene / rGO aerogel composite material with excellent electromagnetic wave attenuation performance, which has obvious advantages in the field of electromagnetic wave absorption as an absorbing material.
[0054] The technical solution of this patent is described in detail below in conjunction with specific embodiments and drawings, and this embodiment does not constitute a limitation to this patent.
[0055] Embodiment 1:
[0056] (1) Ti3C2T x MXene and GO were added into 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed dispersion of the two.
[0057] (2) Add hydrochloric acid solution dropwise to the mixed dispersion to adjust the pH value to 4, and continue ultrasonication for 10 minutes to obtain an acidic mixed solution.
[0058] (3) The acidic mixture was quickly frozen using liquid nitrogen for 20 min, and the frozen solid was then quickly transferred to a freeze dryer for 40 h at a vacuum degree of 3 Pa and a temperature of -30 °C to obtain a three-dimensional MXene / GO aerogel composite material.
[0059] (4) Using infrared light to restore three-dimensional Ti3C2T xMXene / GO aerogel composite material, the irradiation time was 10s, and a three-dimensional MXene / rGO aerogel composite material was obtained.
[0060] (5) The complex dielectric constant and complex magnetic permeability of the three-dimensional MXene / rGO aerogel composite material were tested by vector network analyzer: the three-dimensional MXene / rGO aerogel composite material was mixed with paraffin with a filling amount of 15%; the mixture of the two was molded into a coaxial test ring (thickness: 2mm, inner diameter: 3mm, outer diameter: 7mm), and electromagnetic parameter tests were carried out. Based on the test results, a three-dimensional reflection loss diagram was drawn.
[0061] Embodiment 2:
[0062] (1) Ti3C2T x MXene and GO were added into 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed dispersion of the two.
[0063] (2) Add hydrochloric acid solution dropwise to the mixed dispersion to adjust the pH value to 4, and continue ultrasonication for 10 minutes to obtain an acidic mixed solution.
[0064] (3) The acidic mixture was quickly frozen using liquid nitrogen for 20 min, and the frozen solid was then quickly transferred to a freeze dryer for 40 h at a vacuum degree of 3 Pa and a temperature of -30 °C to obtain a three-dimensional MXene / GO aerogel composite material.
[0065] (4) The three-dimensional MXene / GO aerogel composite material was reduced by infrared light irradiation for 10 s to obtain a three-dimensional MXene / rGO aerogel composite material.
[0066] (5) The complex dielectric constant and complex magnetic permeability of the three-dimensional MXene / rGO aerogel composite material were tested by vector network analyzer: the three-dimensional MXene / rGO aerogel composite material was mixed with paraffin with a filling amount of 15%; the mixture of the two was molded into a coaxial test ring (thickness: 2mm, inner diameter: 3mm, outer diameter: 7mm), and electromagnetic parameter tests were carried out. Based on the test results, a three-dimensional reflection loss diagram was drawn.
[0067] Embodiment 3:
[0068] (1) Ti3C2T x MXene and GO were added into 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed dispersion of the two.
[0069] (2) Add hydrochloric acid solution dropwise to the mixed dispersion to adjust the pH value to 4, and continue ultrasonication for 10 minutes to obtain an acidic mixed solution.
[0070] (3) The acidic mixture was quickly frozen using liquid nitrogen for 20 min, and the frozen solid was then quickly transferred to a freeze dryer for 40 h at a vacuum degree of 3 Pa and a temperature of -30 °C to obtain a three-dimensional MXene / GO aerogel composite material.
[0071] (4) The three-dimensional MXene / GO aerogel composite material was reduced by infrared light irradiation for 10 s to obtain a three-dimensional MXene / rGO aerogel composite material.
[0072] (5) The complex dielectric constant and complex magnetic permeability of the three-dimensional MXene / rGO aerogel composite material were tested by vector network analyzer: the three-dimensional MXene / rGO aerogel composite material was mixed with paraffin with a filling amount of 15%; the mixture of the two was molded into a coaxial test ring (thickness: 2mm, inner diameter: 3mm, outer diameter: 7mm), and electromagnetic parameter tests were carried out. Based on the test results, a three-dimensional reflection loss diagram was drawn.
[0073] Embodiment 4:
[0074] (1) Ti3C2T x MXene and GO were added into 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed dispersion of the two.
[0075] (2) Add hydrochloric acid solution dropwise to the mixed dispersion to adjust the pH value to 5, and continue ultrasonication for 10 minutes to obtain an acidic mixed solution.
[0076] (3) The acidic mixture was quickly frozen using liquid nitrogen for 20 min, and the frozen solid was then quickly transferred to a freeze dryer for 40 h at a vacuum degree of 3 Pa and a temperature of -30 °C to obtain a three-dimensional MXene / GO aerogel composite material.
[0077] (4) The three-dimensional MXene / GO aerogel composite material was reduced by infrared light irradiation for 10 s to obtain a three-dimensional MXene / rGO aerogel composite material.
[0078] (5) The complex dielectric constant and complex magnetic permeability of the three-dimensional MXene / rGO aerogel composite material were tested by vector network analyzer: the three-dimensional MXene / rGO aerogel composite material was mixed with paraffin with a filling amount of 15%; the mixture of the two was molded into a coaxial test ring (thickness: 2mm, inner diameter: 3mm, outer diameter: 7mm), and electromagnetic parameter tests were carried out. Based on the test results, a three-dimensional reflection loss diagram was drawn.
[0079] Embodiment 5:
[0080] (1) Ti3C2T x MXene and GO were added into 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed dispersion of the two.
[0081] (2) Add hydrochloric acid solution dropwise to the mixed dispersion to adjust the pH value to 6, and continue ultrasonication for 10 minutes to obtain an acidic mixed solution.
[0082] (3) The acidic mixture was quickly frozen using liquid nitrogen for 20 min, and the frozen solid was then quickly transferred to a freeze dryer for 40 h at a vacuum degree of 3 Pa and a temperature of -30 °C to obtain a three-dimensional MXene / GO aerogel composite material.
[0083] (4) The three-dimensional MXene / GO aerogel was reduced by infrared light irradiation for 10 s to obtain a three-dimensional MXene / rGO aerogel composite material.
[0084] (5) The complex dielectric constant and complex magnetic permeability of the three-dimensional MXene / rGO aerogel composite material were tested by vector network analyzer: the three-dimensional MXene / rGO aerogel composite material was mixed with paraffin with a filling amount of 15%; the mixture of the two was molded into a coaxial test ring (thickness: 2mm, inner diameter: 3mm, outer diameter: 7mm), and electromagnetic parameter tests were carried out. Based on the test results, a three-dimensional reflection loss diagram was drawn.
[0085] Embodiment 6:
[0086] (1) Ti3C2T x MXene and GO were added into 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed dispersion of the two.
[0087] (2) Add hydrochloric acid solution dropwise to the mixed dispersion to adjust the pH value to 6, and continue ultrasonication for 10 minutes to obtain an acidic mixed solution.
[0088] (3) The acidic mixture was quickly frozen using liquid nitrogen for 20 min, and the frozen solid was then quickly transferred to a freeze dryer for 40 h at a vacuum degree of 3 Pa and a temperature of -30 °C to obtain a three-dimensional MXene / GO aerogel composite material.
[0089] (4) The three-dimensional MXene / GO aerogel composite material was reduced by infrared light irradiation for 20 s to obtain a three-dimensional MXene / rGO aerogel composite material.
[0090] (5) The complex dielectric constant and complex magnetic permeability of the three-dimensional MXene / rGO aerogel composite material were tested by vector network analyzer: the three-dimensional MXene / rGO aerogel composite material was mixed with paraffin with a filling amount of 15%; the mixture of the two was molded into a coaxial test ring (thickness: 2mm, inner diameter: 3mm, outer diameter: 7mm), and electromagnetic parameter tests were carried out. Based on the test results, a three-dimensional reflection loss diagram was drawn.
[0091] Embodiment 7:
[0092] (1) Ti3C2T x MXene and GO were added into 100 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed dispersion of the two.
[0093] (2) Add hydrochloric acid solution dropwise to the mixed dispersion to adjust the pH value to 6, and continue ultrasonication for 10 minutes to obtain an acidic mixed solution.
[0094] (3) The acidic mixture was quickly frozen using liquid nitrogen for 20 min, and the frozen solid was then quickly transferred to a freeze dryer for 40 h at a vacuum degree of 3 Pa and a temperature of -30 °C to obtain a three-dimensional MXene / GO aerogel composite material.
[0095] (4) The three-dimensional MXene / GO aerogel composite material was reduced by infrared light irradiation for 30 seconds to obtain a three-dimensional MXene / rGO aerogel composite material.
[0096] (5) The complex dielectric constant and complex magnetic permeability of the three-dimensional MXene / rGO aerogel composite material were tested by vector network analyzer: the three-dimensional MXene / rGO aerogel composite material was mixed with paraffin with a filling amount of 15%; the mixture of the two was molded into a coaxial test ring (thickness: 2mm, inner diameter: 3mm, outer diameter: 7mm), and electromagnetic parameter tests were carried out. Based on the test results, a three-dimensional reflection loss diagram was drawn.
[0097] Comparative Example 1:
[0098] The process is basically the same as Example 1, except that MXene is not added in step (1).
[0099] Comparative Example 2:
[0100] The method is basically the same as Example 1, except that no hydrochloric acid solution is added in step (2) to adjust the pH.
[0101] Comparative Example 3:
[0102] The method is basically the same as Example 1, except that the infrared light irradiation reduction is not performed in step (4).
[0103] Figure 1 (a) clearly shows that the MXene / rGO aerogel composite material prepared in Example 1 presents a three-dimensional aerogel structure, in which two-dimensional rGO and two-dimensional MXene nanosheets are combined with each other. X-ray diffraction (XRD) pattern ( Figure 1 (b) shows that characteristic peaks of rGO and MXene appeared in the MXene / rGO aerogel composite sample prepared in Example 1, indicating that GO has been successfully reduced and a composite material of rGO and MXene has been formed. Figure 1 (c) shows the three-dimensional reflection loss diagram of the three-dimensional MXene / rGO aerogel composite material prepared in Example 1 in the frequency range of 2.0 GHz to 18.0 GHz. The results show that at an extremely thin thickness of only 1.52 mm, the minimum reflection loss (RL) of the three-dimensional MXene / rGO aerogel composite material reaches -55.23 dB, and the absorption rate exceeds 99.999%. These results prove that the three-dimensional MXene / rGO aerogel composite material of the present invention has excellent electromagnetic wave absorption performance.
[0104] Example 2 and Example 3 are substantially the same as Example 1, except that the weight ratios of MXene and GO are 30 wt %:70 wt % and 50 wt %:50 wt %, respectively. Figure 2 and Figure 3 Three-dimensional reflection loss diagrams of the three-dimensional MXene / rGO aerogel composite materials prepared in Example 2 and Example 3, respectively.
[0105] Figure 2 and Figure 3 It shows that when the mass ratio of MXene to GO is 30wt%:70wt% and 50wt%:50wt%, the minimum reflection loss (RL) of the obtained three-dimensional MXene / rGO aerogel composite material is -54.3dB and -51.6dB, respectively, showing excellent electromagnetic wave absorption performance. This shows that within a certain mass ratio range, the three-dimensional MXene / rGO aerogel composite material can maintain stable electromagnetic wave absorption performance.
[0106] Example 4 and Example 5 are basically the same as Example 3, except that the pH values of the mixed dispersion are adjusted to 5 and 6, respectively. Example 6 and Example 7 are basically the same as Example 5, except that the irradiation time of the infrared lamp is 20s and 30s, respectively.
[0107] The electromagnetic parameters of the three-dimensional MXene / rGO aerogel composites prepared in Examples 4 to 7 were tested and three-dimensional reflection loss diagrams were drawn, respectively. Figures 4 to 7 , the minimum reflection loss of Example 4 is -60.1dB, the minimum reflection loss of Example 5 is -51.35dB, and the minimum reflection loss of Example 6 is -50.1dB. The minimum reflection loss of Example 7 is -49.8dB. By comparing the results of Examples 4 to 7, it can be seen that the present invention can effectively regulate the absorbing properties of the three-dimensional MXene / rGO aerogel composite material by regulating the pH value of the mixed dispersion of MXene and GO and the irradiation time of the infrared lamp, thereby obtaining excellent absorbing properties.
[0108] Figure 8 (a) is the XRD spectrum of the product prepared in Comparative Example 1, which only has the characteristic peak of GO. The three-dimensional reflection loss diagram of the GO material in Comparative Example 1 is as follows: Figure 8 As shown in (b), it can be seen that the minimum reflection loss of the GO material prepared in Comparative Example 1 is only -21.08 dB, which further verifies that the introduction of MXene significantly improves the wave absorption performance of the GO material, and the obtained three-dimensional MXene / rGO aerogel composite material has excellent wave absorption performance.
[0109] Fig. 9 The three-dimensional reflection loss diagram of the three-dimensional MXene / rGO aerogel composite material prepared in Comparative Example 2 is shown, and its minimum reflection loss is -43.8 dB. It can be seen that compared with Example 1, the dimensional matching between MXene and rGO cannot be effectively achieved without adjusting the pH value of the system, resulting in a decrease in its wave absorption performance.
[0110] Fig.10 (a) is the XRD spectrum of the product prepared in Comparative Example 3. It can be seen from the figure that GO is not reduced, indicating that GO cannot be reduced without infrared irradiation. Fig.10 (b) is a three-dimensional reflection loss diagram of the product prepared in Comparative Example 3. It can be seen that the minimum reflection loss of the product prepared in Comparative Example 3 is only -39.3 dB, which further verifies that infrared irradiation can effectively promote the reduction of GO and prepare a three-dimensional MXene / rGO aerogel composite material with excellent wave absorbing properties.
Claims
1. A method for preparing a MXene / rGO aerogel composite material, characterized in that: The following steps are involved: S1, adding MXene and GO into water and dispersing them by ultrasonic to obtain a mixed dispersion; S2, adding an acidic reagent dropwise to the mixed dispersion, adjusting the pH to 4-6, and dispersing by ultrasonication to obtain an acidic mixed solution; S3, freeze-drying the acidic mixed solution to obtain a three-dimensional MXene / GO aerogel composite material; S4, subjecting the three-dimensional MXene / GO aerogel composite material to infrared light irradiation treatment to obtain a three-dimensional MXene / rGO aerogel composite material.
2. The method for preparing the MXene / rGO aerogel composite material according to claim 1, characterized in that: In S1, the mass ratio of MXene and GO is (10~50):(90~50).
3. The method for preparing the MXene / rGO aerogel composite material according to claim 1, characterized in that: The MXene is Ti3C2T x .
4. The method for preparing the MXene / rGO aerogel composite material according to claim 1, characterized in that: In S1, the ultrasonic dispersion time is 10 to 30 minutes.
5. The method for preparing the MXene / rGO aerogel composite material according to claim 1, characterized in that: In S2, the acidic reagent is a hydrochloric acid solution.
6. The method for preparing the MXene / rGO aerogel composite material according to claim 1, characterized in that: In S2, the ultrasonic dispersion time is 10 to 30 minutes.
7. The method for preparing the MXene / rGO aerogel composite material according to claim 1, characterized in that: In S3, the freeze-drying conditions are: vacuum degree of 3 to 10 Pa, temperature of -30 to -40°C, and freeze-drying time of 40 to 60 h.
8. The method for preparing the MXene / rGO aerogel composite material according to claim 1, characterized in that: In S4, the infrared light irradiation treatment time is 10 to 30 seconds.
9. A MXene / rGO aerogel composite material obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the MXene / rGO aerogel composite material according to claim 9 as an absorbing material in electromagnetic wave absorption.
